"One Nation Under God": The System‐Justifying Function of Symbolically Aligning God and Government. Issue 5 (29th July 2016) - Shepherd, Steven; Eibach, Richard P.; Kay, Aaron C.
Abstract : Do references to God in political discourse increase confidence in the U.S. sociopolitical system? Using a system justification framework (Jost & Banaji, 1994 ), five studies provide evidence that, (1) increasingly governments symbolically associate the nation with God when public confidence in the social system may be threatened and (2) associating the nation with God serves a system‐justifying function by increasing public confidence in the system. In an analysis of U.S. presidential speeches, presidents were more likely to symbolically associate the nation with God during threatening times (Study 1). Among religious individuals, referencing God in political rhetoric increased the perceived trustworthiness of politicians, compared to patriotic secular rhetoric (Study 2) or simply priming the concept of God (Study 3). These effects were also unique to politicians from one's own sociopolitical system (Study 4). Finally, believing God has a plan for the United States attenuates the deleterious effect that perceptions of national decline have on system confidence (Study 5). Implications for the system‐justifying function of religion are discussed.